1997
DOI: 10.1007/s002990050292
|View full text |Cite
|
Sign up to set email alerts
|

Production of diosgenin by hairy root cultures of Trigonella foenum-graecum L.

Abstract: Hairy root cultures of Trigonella foenum-graecum L. were established with Agrobacterium rhizogenes strain A 4 . The hairy roots produce diosgenin, an important spirostanol for the semi-synthesis of steroid hormones. Fourteen different liquid media were investigated. The fastest growth was obtained in McCown's woody plant (WP) medium supplemented with 3% sucrose; the highest diosgenin content was observed in half-strength WP medium with 1% sucrose (0.040% dry weight), which represents almost twice the amount de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 10 publications
(10 reference statements)
4
20
0
1
Order By: Relevance
“…as obtained from 20-d-old root culture. Similar to the present results, better growth and higher diosgenin accumulation in Trigonella foenum-graecum hairy roots (Merkli et al 1997) was observed in lower pH (5.0 and 4.8 before and after autoclaving, respectively) in comparison with that grown in higher pH such as 5.5 and 5.9. Although several investigations have been made on influence of pH on growth and secondary metabolite formation in hairy roots of different plant species (Mukundan and Hjorsto 1991), the results regarding this aspect are not clear.…”
Section: ⎯⎯⎯⎯supporting
confidence: 93%
“…as obtained from 20-d-old root culture. Similar to the present results, better growth and higher diosgenin accumulation in Trigonella foenum-graecum hairy roots (Merkli et al 1997) was observed in lower pH (5.0 and 4.8 before and after autoclaving, respectively) in comparison with that grown in higher pH such as 5.5 and 5.9. Although several investigations have been made on influence of pH on growth and secondary metabolite formation in hairy roots of different plant species (Mukundan and Hjorsto 1991), the results regarding this aspect are not clear.…”
Section: ⎯⎯⎯⎯supporting
confidence: 93%
“…Importance of fenugreek seeds pretreatment SC-CO 2 extraction of fenugreek seeds without both steps of pretreatment (defatting and hydrolysis) showed that diosgenin was not present in the collected extract. Importance of hydrolysis was also reported in literature [15][16][17][18] and this study proved that hydrolysis was the main step for pretreatment of fenugreek seeds necessary for diosgenin isolation by SC-CO 2 extraction.…”
Section: Resultssupporting
confidence: 67%
“…Seeds contain 1-2% steroidal sapogenins, mainly diosgenin contained in the plant as steroidal saponin glycoside. Generally, the extraction methods of diosgenin from fenugreek seeds require pretreatment of the plant including defatting as the first step, followed by acid hydrolysis with aim to prepare corresponding hydro-isolate [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This evidence suggests that the biosynthesis of secondary metabolite increased during the stationary phase of growth. Similar observations have been noted for other hairy root cultures (Bhadra and Shanks, 1997;Merkli et al, 1997;Sasaki et al, 1998;Kittipongpatana et al, 2002). Increased production of secondary metabolite at the stationary phase might be come from the stress of tissue due to the change of environment such as undernourishment.…”
Section: Resultssupporting
confidence: 72%